STUDI TATALAKSANA PEMELIHARAAN ANGSA DI PESISIR DANAU TONDANO - Rini Leke (EKOTON, 2014)
Coastal Tondano Lake is a very suitable area for the development of waterfowl because of supported by the availability of feed and grazing land. Classified as waterfowl goose that great potential if developed in the area. But the reality on the ground despite maintenance supported by the geese on land and feed potential, development and the longer the goose population is declining or growing less so to see the maintenance of the system in an effort to increase the population of geese on the lake shore Tondano. Based on these two aims of research conducted to obtain information about the goose that tatalaksanan maintenance applies to farmers in the coastal lake Tondano. This research has been conducted in five districts in the coastal lakes Tondano using survey methods through direct observation in the field, while the determination of the total respondents use the sampling method or a complete count of all the farmers who take care of geese on the lake shore Tondano. Data obtained in the analysis with a descriptive analysis. From the results of the study concluded that the procedure of raising geese on the lake shore Tondano still traditional, this is due to the application of technology related to seed, marriage, food, cages and the disease is still low.